Magnesium for dynamic nanoplasmonics - Duan, Xiaoyang; Liu, Na (Accounts of chemical research, 2019)
ConspectusThe key component of nanoplasmonics is metals. For a long time, gold and silver have been the metals of choice for constructing plasmonic nanodevices because of their excellent optical properties. However, these metals possess a common characteristic, i.e., their optical responses are static. The past decade has been witnessed tremendous interest in dynamic control of the optical properties of plasmonic nanostructures. To enable dynamic functionality, several approaches have been proposed and implemented. For instance, plasmonic nanostructures can be fabricated on stretchable substrates or on programmable templates so that the interactions between the constituent metal nanoparticles and therefore the optical responses of the plasmonic systems can be dynamically changed. Also, plasmonic nanostructures can be embedded in tunable dielectric materials, taking advantage of the sensitive dependence of the localized surface plasmon resonances on the neighboring environment. Another approach, which is probably the most intriguing one, is to directly regulate the carrier densities and dielectric functions of the metals themselves.In this Account, we discuss a relatively new metal in nanoplasmonics, magnesium, and its important role in the development of dynamic plasmonic nanodevices at visible frequencies. We first elucidate the basic optical properties of Mg and compare it with conventional plasmonic materials such as Au, Ag, and others. Then we describe a unique characteristic of Mg, i.e., its reversible phase transitions between the metallic state and a dielectric state, magnesium hydride, through hydrogenation and dehydrogenation. This sets the basis for Mg in dynamic nanoplasmonics. In particular, the structural properties and dielectric functions of the two distinct states are discussed in detail. Subsequently, we highlight the experimental investigations of the physical mechanisms and nanoscale understanding of Mg nanoparticles during hydrogenation and dehydrogenation. We then introduce a plethora of newly developed Mg-based dynamic optical nanodevices for applications in plasmonic chirality switching, dynamic color displays with Mg nanoparticles and films, and dynamic metasurfaces for ultrathin and flat optical elements. We also outline strategies to enhance the stability, reversibility, and durability of Mg-based nanodevices. Finally, we end this Account by outlining the remaining challenges, possible solutions, and promising applications in the field of Mg-based dynamic nanoplasmonics. We envision that Mg-based dynamic nanoplasmonics will not only provide insights into understanding the catalytic processes of hydrogen diffusion in metals by optical means but also will open an avenue toward functional plasmonic nanodevices with tailored optical properties for real-world applications.